Peningkatan Hasil Bimbingan TIK Siswa melalui Penggunaan E-learning - Muttaqin Kholis Ali (IICET (Indonesian Institute for Counseling, Education and Therapy), 2021)
The purpose of this research is to determine the increase in ICT learning outcomes through the application of E-Learning in class X MIA 1 students at SMA Negeri 1 Tambangan. The research method used is quasi experimental with a pretest-posttest control group design. The research divides the control class using conventional learning media and the experimental class using E-Learning media. The data analysis method is descriptive quantitative. The results obtained from this research is that the applied E-Learning can improve student’s learning achievement. It is evident from the pretest and posttest mean scores which increased from 67.03 to 86.09. The application of E-Learning is also more effective than the application of conventional learning, as evidenced by the normalized gain value of the experimental class of g = 0.54 is higher than the gain value of the control class of g = 0.30. Besides, the results of the posttest hypothesis test with t-test showed P (0.006) < ∝ (0.05) so that the research hypothesis is accepted. The conclusion obtained from this research is that the application of the E-Learning can improve the ICT learning achievement of class X MIA 1 SMA Negeri 1 Tambangan.